Distribution of sound intensity level of frequency responses of a room - OZIMEK, Edward (Archives of Acoustics, 1984)
In a number of investigations on the quantitative evaluation of the behaviour of the frequency response of a room, it has been assumed that above some boundary frequency this behaviour can be regarded as the result of a random process of summing up of reflected waves with an intensity level distribution close to a normal one. In the literature there is however lack of papers. which confirm experimentally the correctness of this assumption or indicate its possible deviations from practical conditions. In view of this, investigations were undertaken to determine the form of the function of distribution of sound intensity level changes for a number of frequency responses registered in a few selected rooms (models) with varying acoustic properties. The investigation results obtained show that the functions of distribution of intensity level changes for these responses do sometimes differ a great deal from the normal one. This testifies that over the range of model investigations for which all the required conditions are satisfied, the assumption of a normal (Gaussian) distribution of the energy of reflected waves is not fulfilled.